Thrombin generation test as a useful tool for improving disease severity stratification in antiphospholipid syndrome - Eric Hachulla; Julien Labreuche; David Launay; Marc Lambert; Cecile Yelnik; Marie Frimat; Sylvain Dubucquoi; Anne Bauters; Maximilien Desvages; Steve Lancel (RMD Open)
Background Patients with antiphospholipid syndrome (APS) display a wide range of clinical manifestations with similar immunological profile with the presence of lupus anticoagulant in around 70% of them. Although antiphospholipid antibodies (aPL) profile influences the risk of thrombosis in APS, APS risk stratification remains to be improved.Objectives Our study aimed to evaluate thrombin generation test (TGT) interest to improve disease severity stratification in APS patients.Patients/methods In this monocentric, transversal study, we included unselected primary thrombotic APS patients, fulfilling APS classification criteria and treated by vitamin K antagonist (VKA). 28 non-APS patients under VKA followed in our hospital were included as controls. TGT was performed on plasma samples with the calibrated automated thrombogram in our core laboratory.Results Between January 2020 and March 2023, 114 thrombotic APS patients (without systemic lupus erythematosus) were included (female 71 (62.3%), mean age 50±14 years old, median duration since the last APS event of 51 months (IQR 23–129 months)). APS patients had prolonged lag time (LT) and time to peak (TTP) compared with anticoagulated controls. History of relapse, catastrophic APS (CAPS), all aPL positivities and elevated Bb fragments were strongly associated with a prolonged LT and TTP.Conclusions Our findings suggest that APS patients under VKA had significantly prolonged TGT times compared with anticoagulated controls, with the greatest prolongations in patients with history of relapse or CAPS. Thus, TGT might be a useful tool to improve APS disease severity stratification without temporary cessation of VKA.